Organisasi Masa Depan: Strategi Imperatives dan Core Competencies pada Abad 21 - Susanti, Vivi Ani (Jurnal Widya Manajemen & Akuntansi, 2003)
Globalization causes a new perspective an organization's design. The changes of business environment cause organization control to change from plan and control mode to sense and respond mode. It represent organization provides a service value to the customer. The question is how about the strategy for the 21st century?